Ancestralidad Indígena: desvelando la vida, muerte y renacimiento de los pueblos de la Sierra Nevada de Santa Marta, Colombia - Perilla, Viviana Marcela León (Universidade Federal de São Carlos, 2023)
The literature related to palliative care and indigenous populations generally reports the experiences of first peoples from the northern hemisphere, addressing topics such as dying outside their lands, traditional care, ceremonies, and rituals after death. This material does not always focus on occupations that refer to the affirmation of life or the preparation for death in indigenous communities in Latin America, especially in Colombia. Thus, this study aims to describe the occupational processes at the end of life of Colombian indigenous communities in the Sierra Nevada de Santa Marta. It seeks to reveal the appreciation of non-Eurocentric palliative care, in the construction of individual and collective meanings of the Kankuamo and Arhuaco peoples around the processes of death, dying and mourning. Under a decolonial positionality, community contemplation, alternative conversation and configurative reflection are integrated as guiding actions that accompany native science, using Tejido/Yarning, as a resource based on respect, freedom, reciprocity, specificity, inclusion and cultural safety. Through seven purposes: therapeutic, social, family, intercultural, investigative, collaborative and relational, feelings were woven with the Mayoras, spiritual authorities (Mamus, Akumama), bereaved families and indigenous children. Themes related to care in the face of the processes of death were intertwined; the cosmological origin of death and its payments; postmortem ancestral ceremonies such as "seeding" and "eysa/mortuoria"; the reframing of pain in the face of loss; ways of intercultural learning about death and dying; as well as Mother Earth, spirituality and religion, reflecting on the meanings of their collective, ancestral and traditional memories toward the end of life. Thus, the study can be a contribution to history and intercultural dialogues, to broaden the understanding of health professionals, notably occupational therapists, about the culturally safe occupational dimension of death, dying and mourning based on the feelings and actions of indigenous communities.

La literatura relacionada con los cuidados paliativos y las poblaciones indígenas generalmente reporta las experiencias de los pueblos del hemisferio norte, abordando temas como morir fuera de sus tierras, cuidados tradicionales, ceremonias y rituales después de la muerte. Este material no siempre prioriza ocupaciones que se refieren a la afirmación de la vida o preparación para la muerte en las comunidades indígenas de América Latina, especialmente en Colombia. Así, el estudio tiene como objetivo describir los procesos ocupacionales al final de la vida de las comunidades indígenas colombianas en la Sierra Nevada de Santa Marta. Busca revelar la apreciación de los cuidados paliativos no eurocéntricos, en la construcción de significados individuales y colectivos de los pueblos Kankuamo y Arhuaco en torno a los procesos de muerte, morir y duelo. Bajo una posicionalidad decolonial, la contemplación comunitaria, la conversación alternativa y la reflexión configurativa se integran como acciones orientadoras que acompañan a la ciencia nativa, utilizando el Tejido/Yarning, como recurso basado en el respeto, la libertad, la reciprocidad, la especificidad, la inclusión y la seguridad cultural. A través de siete propósitos: terapéutico, social, familiar, intercultural, investigativo, colaborativo y relacional, se tejieron sentimientos con las Mayoras, autoridades espirituales (Mamus, Akumama), familias en duelo y niños indígenas. Se entrelazaron temas relacionados con el cuidado ante los procesos de muerte; el origen cosmológico de la muerte y sus pagos; ceremonias ancestrales post mortem como "siembra" y "eysa/mortuoria"; la reformulación del dolor ante la pérdida; formas de aprendizaje intercultural sobre la muerte y el morir; así como la Madre Tierra, la espiritualidad y la religión, reflexionando sobre los significados de sus memorias colectivas, ancestrales y tradicionales al final de la vida. Así, el estudio puede ser una contribución a la historia y los diálogos interculturales, para ampliar la comprensión de los/las profesionales de la salud, en particular de los/ las terapeutas ocupacionales, sobre la dimensión ocupacional culturalmente segura de la muerte, el morir y el duelo a partir de los sentimientos y acciones de las comunidades indígenas.
Ancestralidade Indígena: revelando a vida, morte e renascimento dos povos da Serra Nevada de Santa Marta, Colômbia
Keywords: Indigenous culture; Intercultural health; Occupation; Yarning; End of life; Culture security; Occupational therapy; Cultura indígena; Saúde intercultural; Atitude diante da morte; Ocupação; Tecido; Fim da vida; Segurança da cultura; Terapia ocupacional; Salud intercultural; Actitud frente a la muerte; Ocupación; Fin de vida; Seguridad cultural; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL